Salient ingredients for direct water reclamation from treated municipal wastewater for potable reuse: Diepsloot Township case study - Nemadodzi, Lufuno; Sikhwivhilu, Keneiloe; Jalama, Kalala; Moothi, Kapil; Bambo, Mokae; Mutanga, Shingirirai; Siame, John (Frontiers in Environmental Science, 2023)
Across the world population growth, expansion of economic activities and climate change have become a concern for future water supply. Overcrowded townships in most developing countries experience low water supply. To address the issue, many countries are investigating strategies to augment current water supplies. Water reclamation has been identified as a plausible sustainable solution to meet potable water supply demand, in turn achieving SDG 6.3. This study identifies some of the critical success factors for consideration of municipal waste water reclamation. This was undertaken in the growing township of Diepsloot, in Johannesburg (South Africa). Diepsloot is densely populated with over 350 000 people as recorded in 2022. As a result, water shortages are common due to insufficient bulk water facilities to supply the area. A direct potable water reclamation plant from treated municipal wastewater has been proposed to augment the water supply. Aqueous Material Balance (AqMB)®, a process modelling simulator software for water treatment processes to predict water quality and quantity, was used to design and simulate the water reclamation plant process. Our findings show that, the quantity and quality of water, as well as the choice of treatment technology are key. The simulations treatment process proposed here-in indicated successful removal of the contaminants to acceptable SANS 241:2015 drinking water standards. Furthermore, the plant has the potential to provide 109 L/day of clean water per person for a population of 350 000. Therefore, direct potable water reclamation shows great potential to augment current water supply to support growing populations where natural water sources are scarce.